In vitro-Induced Human IL-10+ B Cells Do Not Show a Subset-Defining Marker Signature and Plastically Co-express IL-10 With Pro-Inflammatory Cytokines - Lighaam, Laura C.; Unger, Peter-Paul A.; Vredevoogd, David W.; Verhoeven, Dorit; Vermeulen, Ellen; Turksma, Annelies W.; ten Brinke, Anja; Rispens, Theo; van Ham, S. Marieke (Frontiers in Immunology, 2018)
Regulatory B cells (Breg) have been described as a specific immunological subsets in several mouse models. Identification of a human counterpart has remained troublesome, because unique plasma membrane markers or a defining transcription factor have not been identified. Consequently, human Bregs are still primarily defined by production of IL-10. In this study, we sought to elucidate if in vitro-induced human IL-10 producing B cells are a dedicated immunological subset. Using deep immune profiling by multicolor flow cytometry and t-SNE analysis, we show that the majority of cells induced to produce IL-10 co-express pro-inflammatory cytokines IL-6 and/or TNFα. No combination of markers can be identified to define human IL-10+TNFα-IL-6- B cells and rather point to a general activated B cell phenotype. Strikingly, upon culture and restimulation, a large proportion of formerly IL-10 producing B cells lose IL-10 expression, showing that induced IL-10 production is not a stable trait. The combined features of an activated B cell phenotype, transient IL-10 expression and lack of subset-defining markers suggests that in vitro-induced IL-10 producing B cells are not a dedicated subset of regulatory B cells.